Faktor-Faktor yang Berhubungan dengan Keikutsertaan Masyarakat Menjadi Peserta BPJS Mandiri - Eko Heryanto; Fera Meliyanti; Sabtian Sarwoko (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
The participation of the Social Security Administering Body (BPJS) is also regulated in Presidential Regulation No. 111 in article 6 that all Indonesian residents are required to be registered as health insurance participants. Data on the number of BPJS participants in OKU Regency in 2020 as many as 218,003 participants, in 2021 as many as 216,387 participants and in 2022 as many as 243,067 participants. Meanwhile, for the Tanjung Baru puskesmas area, the number of BPJS participants in 2020 was 3,782 participants, in 2021 there were 3,745 participants and in 2022 there were 3,888 participants. This study aims to determine the factors related to community participation in becoming independent BPJS participants in Tanjung Baru Village. The research design used was a cross sectional research design. The sample is all heads of families in Tanjung Baru Village, the working area of ??UPTD Tanjung Baru Health Center, OKU Regency in 2022, totaling 2544 families with a sample size of 339 samples. The statistical test used is the chi square test. Based on the univariate analysis, the results obtained were 134 (39.5%) respondents with participant status, as many as 163 (48.1%) respondents with good knowledge, 173 (44.8%) respondents with positive attitudes, as many as 154 respondents (45 .5%) with high income and 159 (46.9%) respondents stated that there was family support. The results of the bivariate analysis obtained the results of the knowledge variable with a p value of 0.001, attitudes with a p value of 0.000, income with a p value of 0.000, and family support with a p value of 0.001. there is a significant relationship between knowledge, attitudes, income and family support with community participation in becoming independent BPJS participants in Tanjung Baru Village.